Tests and Proofs c - Gogolla, Martin; Wolff, Burkhart; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Test and Proofs, TAP 2011, held in Zurich, Switzerland in June/July 2011. The 12 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 27 submissions. Among the topics covered are model checking, testing systems, test generation, symbolic testing, SAT solvers, SMT solvers, property-based testing, automated test generation, learning based testing, UML, OCL, specification-based testing, and network testing.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Software Engineering; Programming Techniques; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Programming Languages, Compilers, Interpreters